iBEST (IRC Booking and Event Management Systems) - Abdul Karim, Siti Nurbaya; Yunus, Amirul Hariz (Universiti Teknologi MARA, Kedah, 2017)
iBEST (IRC Booking and Event Management Systems) is an online booking system that provides online service to all IRC users. Users can search, reserve or cancel an existing booking via online. To date, IRC has six (6) discussion rooms, two (2) training zone and an auditorium that can be booked by users. Users can also make an appointment with librarian and register for IRC event. Besides, it also helps librarian to manage booking facilities and event, use gathered data onto reporting as well as on planning for library promotion/marketing. iBEST also helps IRC to enhance the services efficiency, improve the service experience as well as to provide 24/7 services to users.